SINERGITAS PERAN KOMITE DAN KEPALA MADRASAH DALAM PROSES PENCAPAIAN MUTU PENDIDIKAN - Nurmiati Nurmiati; Dirham Dirham; Izza Fadhlinah Dirham; Alauddin Alauddin (Kelola: Journal of Islamic Education Management, 2022)
This article discusses the synergistic role of the committee and the head of the madrasa in the process of achieving the quality of education at Madrasah Aliyah Negeri Palopo. This study aims: to determine the form of synergy between the committee and the head of the madrasa in the process of achieving the quality of education in Madrasah Aliyah Negeri Palopo and to determine the indicators of education quality in Madrasah Aliyah Negeri Palopo. The type of research used is descriptive qualitative. The sources of research data are madrasa committees, madrasa heads, and teachers. Data obtained through observation, interviews and documentation. Furthermore, the data for checking the validity of the research data were triangulated with sources.The results of this study indicate that the Madrasah Committee has synergized with the madrasah principal regarding its role as a consideration, supporter, controller, and mediator in the process of achieving quality education at Madrasah Aliyah Negeri Palopo. However, in carrying out the duties of the madrasa committee as representatives of the community, it has not been maximized, such as the implementation of its role in accommodating complaints from the community and there are still tasks and functions that have not been carried out, namely giving consideration to madrasa cooperation with other parties. Regarding the indicators of the quality of education at Madrasah Aliyah Negeri Palopo, it includes the management of its inputs (the process of accepting new students), the educational process (the learning process), and its output (which includes the quality of graduates achieved both academic and non-academic achievements).